2012
DOI: 10.1071/sh11155
|View full text |Cite
|
Sign up to set email alerts
|

Anal sex and associated HIV-related sexual risk factors among female sex workers in Andhra Pradesh, India

Abstract: Abstract. Background: This study aims to understand the correlates of anal sex practices among female sex workers (FSWs) and examine the association of anal sex with HIV-related sexual risk factors in Andhra Pradesh, India. Methods: A cross-sectional behavioural survey was conducted in 2011 among 795 FSWs aged 18 years or older. Probability-based cluster sampling was used to select respondents from sex work hotspots. Results: One-quarter (23%) of FSWs had practiced anal sex in the last year. The odds of practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
1
25
2
Order By: Relevance
“…We used the binomial distribution and logit link, and report odds ratios (OR) for dichotomous outcome variables (consistent condom use with paying partners, consistent condom use with non-paying partners, sex while high, PSA+ or ATS+). Multivariate analyses included all three violence exposures (moderate physical, severe physical, and sexual) and known and hypothesized confounders: age, education, marital status, and past month sex work venue (Argento et al, 2014; Beattie et al, 2010; Couture et al, 2011; Hong et al, 2013; Patra et al, 2012; Surratt et al, 2012). Since our a priori hypothesis was that violence exposed women would have increased HIV risk even in the presence of ATS use, we adjusted each sexual risk model for self-reported days of ATS use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the binomial distribution and logit link, and report odds ratios (OR) for dichotomous outcome variables (consistent condom use with paying partners, consistent condom use with non-paying partners, sex while high, PSA+ or ATS+). Multivariate analyses included all three violence exposures (moderate physical, severe physical, and sexual) and known and hypothesized confounders: age, education, marital status, and past month sex work venue (Argento et al, 2014; Beattie et al, 2010; Couture et al, 2011; Hong et al, 2013; Patra et al, 2012; Surratt et al, 2012). Since our a priori hypothesis was that violence exposed women would have increased HIV risk even in the presence of ATS use, we adjusted each sexual risk model for self-reported days of ATS use.…”
Section: Methodsmentioning
confidence: 99%
“…Violence exposed women engaged in sex work report more frequent anal sex (Patra et al, 2012), higher numbers of sex partners (Go et al, 2011), less frequent condom use (Beattie et al, 2010; Go et al, 2011) and are at higher risk of sexually transmitted infections than those who have not experienced recent violence (Shannon et al, 2014). Violence is also associated with increased alcohol (Surratt, 2007), illegal drug use (Hong et al, 2013; Surratt, 2007), including marijuana and cocaine (Surratt, 2007) as well as injection drug use (Ulibarri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, reports from scientific research indicate a positive association between alcohol consumption and HIV risk [7], [11][15]. Moreover, FSWs who consume alcohol are more likely to engage in anal sex than those who do not [10], [16]. Recent advances in HIV research have also highlighted concurrent sexual relationship as another important factor in increasing the rate of infection in a population [5], [6], [17].…”
Section: Introductionmentioning
confidence: 97%
“…However, a growing body of literature suggests that in addition to condom use, practices such as anal sex and alcohol consumption, and the nature of sexual partnerships (single, sequential, multiple or concurrent multiple relationships), are factors that also need attention [1][6]. Empirical research suggests that, the practice of anal sex, even with a condom, can increase the chances of getting sexually transmitted infections (STIs) and/or HIV [7][10]. Similarly, reports from scientific research indicate a positive association between alcohol consumption and HIV risk [7], [11][15].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has shown that on most occasions, FSWs tend to agree to sex, as well as to varieties of sexual acts such as anal sex and oral sex, if clients pay them more money. 37 However, FSWs' noncommercial relationships may be of a romantic nature and hence they may have a chance to choose sexual partners. Nevertheless, in both types of relationships, assortativeness is very low.…”
Section: Discussionmentioning
confidence: 99%